Menstrual hygiene: Knowledge and practice among adolescent school girls at Koawena, Ende district-Indonesia - Martina Bedho; Anatolia K Doondori; Irwan Budiana (Malahayati International Journal of Nursing and Health Science, 2020)
Background: World Health Organization global database on women rarely pay attention to the cleanliness of their external genitalia, resulting in annual vaginal infections 10-15% by candida and 15% vaginal discharge. In Indonesia was a very few study on menstrual hygiene: knowledge and practice among adolescentPurpose: Knowing the influence of counseling on menstrual hygiene: knowledge and practice among adolescent school girls at Koawena, Ende district-IndonesiaMethods: The quantitative research by quasi-experiment design of one-group pretest-posttest approach. The population was adolescent school girls at Koawena, Ende district-Indonesia by total sampling were 17 respondents. Conducted on August, 2018. The analysis used univariate and bivariate analysis using the  paired T- test.Results: The bivariate test analysis showed differences in the level of knowledge before and after counseling on menstrual hygiene: knowledge and practice p-value = 0.034, indicating by increasing of the level of knowledge, would be followed by in a good practice in menstrual hygiene among adolescent school girls at Koawena, Ende district-Indonesia.Conclusion: The health practitioners need to come to adolescent school girls to give health education with the topic of menstrual hygiene: knowledge and practice.